The European Convention Law and the Police - Bjelopoljak, Ahmed (Kriminalističke teme, 2017)
Reason for writing and research problem(s): In modern democratic countries, the police is a unique institution of government’s authority with powerful and efficient mechanisms for use of force for the protection of the community, which ability at the same time presents a risk of violating human rights. These modern democracies train the members of their police forces to be aware that powers they possess can only be used in accordance with the Constitution and the law. Simultaneously, these countries try to develop institutions within their system of government to oversee the legality of police work. The foundation of the European human rights protection framework is the European Convention for the Protection of Human Rights and Fundamental Freedoms (hereinafter ECHR), which over the years developed into the most dominant among international systems for protection of human rights (lex specialis). My extensive experience working in the police force has inspired me to prepare an overview of issues regarding protection of individuals’ rights and freedoms through actions of police officers while performing their duties. Purpose of the paper: The purpose of this paper is to provide an overview of the European law dealing with police work which is based upon the ECHR and the decisions of the European Court of Human Rights (hereinafter ECtHR) which function stems from the purpose and the legal nature of the ECHR. Methodology/Design: To achieve the stated purpose, this paper will employ the theoretical analysis of the relevant provisions of the ECHR and the decisions of the ECtHR regarding police work. Research/Paper limitations: The paper will be mostly limited to more important parts and provisions of the Convention which are relevant to the police work. Results/Findings: The results of this work should show that police officers serve a purpose greater than themselves and that they are not above the law, but rather they are supposed to enforce the domestic law as well as the international human rights law, and by doing so they protect themselves in the performance of their duties as well as their own rights and those of their fellow citizens, even if this means that the efficiency of the police work will sometimes be impeded. General conclusions: Police officers’ work has many duties and obligations which requires every police officer to understand the domestic and international human rights standards in exercising their everyday duties. Research/Paper Validity: This paper further intends to stimulate police officers, especially those in charge of training and education, to develop and deepen their understanding of human rights through further training.